THE PLACE AND ROLE OF THE LENDING SYSTEM IN SUPPORTING FAMILY BUSINESS ACTIVITIES IN UZBEKISTAN - Dilshodbek Yuldashevich Khamrakulov (Journals Park Publishing, 2024)
In this article, as a result of the reforms carried out in Uzbekistan during the years of independence, the growth dynamics of family business entities, the practical results of the subsidies allocated to them by the state and the lending policy implemented by commercial banks, the volume of products produced by Ferghana Valley entrepreneurs based on primary sources, archival materials and literature analyzed.
Keywords: economy, Ferghana Valley, industry, production, family business, business entities, credit, microcredit, small and medium business, business plan, entrepreneur.